ANALISIS PENGARUH KUALITAS LAYANAN, INTERNET BANKING DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH - Selvi Sumanti Lumban Gaol (Journal of Accounting and Management, 2025)
This study aims to investigate the influence of service quality, BRI Internet Banking, and customer satisfaction on customer loyalty. The research method used is quantitative research. Quantitative research requires quantitative data represented by numbers. The population is BRI customers. The number of respondents was 100. The respondent selection technique used convenience sampling. The sample consisted of customers who have accounts and are actively transacting at BRI. The collected data was then tested for hypothesis analysis using SPSS 21. The results showed that service quality significantly influences customer loyalty. The test results indicate that service quality, internet banking, and customer satisfaction influence (Y) customer loyalty.